Investigation of natural gas energy fraction and injection timing on the performance and emissions of a dual-fuel engine with pre-combustion chamber under low engine load. (1st March 2017) - Yousefi, Amin; Birouk, Madjid
Highlights: Improved cylinder charge as a result of high swirling motion of pre-chamber. Drastic reduction of NOx at 60% natural gas energy fraction compared to diesel mode. Higher unburned methane emissions under dual-fuel operation. 46% decrease of unburned methane emissions by using pre-combustion chamber. Abstract: Energy fraction of the main (premixed) fuel and pilot injection timing are important in dual-fuel pilot diesel ignition engine. In the present study, natural gas, which is the main premixed fuel, is induced into the engine through the intake port, while the pilot diesel fuel (for ignition) is indirectly injected into the engine. A computational fluid dynamic (CFD)-chemistry platform based on AVL FIRE-CHEMKIN is used to simulate the combustion and emissions characteristics of a dual-fuel pilot diesel ignition engine operating on premixed natural gas. The effect of natural gas energy fraction and diesel injection timing at constant engine total fuel energy on combustion performance and emissions is investigated at low engine load (25% load and IMEP = 3 bar). The results revealed that at injection timings of 12 and 20 °BTDC, the maximum ITE (26.7%) occurs at 50% natural gas energy fraction. This is attributed to the improved cylinder charge conditions as a result of high swirling motion produced by the introduction of pre-combustion chamber. Moreover, a drastic reduction of NOx emissions was observed at 60% natural gas energy fraction in comparison with that of only diesel combustion (i.e., 0% natural gas energy fraction). On the other side, the combustion of fuel starts in the pre-combustion chamber and propagates into the main chamber. As a result, the combustion peak temperature drops which significantly reduces NOx formation. The results revealed that unburned methane emissions under dual-fuel operation mode become much higher compared to that under diesel combustion mode, which implies that a considerable amount of gaseous fuel escapes the combustion process at low load. However, using pre-combustion chamber is found to decrease unburned methane emissions by 46% on average compared to dual-fuel engine without pre-combustion chamber.